Factors Related to Self-Protection from COVID-19 Infection among the Residents in Three Southern Border Provinces during the Third Wave Outbreak in 2021 - Pongkaset, Anchalee; Katsara, Kritsanate; Lillahkul, Niratchara; Samaae, Suhaila; Thongloop, Nualpan; Hemtrakoonwong, Rosenanee; Yueroh, Naseeroh; Khatkhamhaeng, Salin; Deraman, Arunothai (Health Science Journal of Thailand, 2023)
This cross-sectional research aimed to study the level of self-protection and the factors related to self-protection from COVID-19 infection among the residents in three southern border provinces during the third wave outbreak in 2021. The research samples were 400 residents. The data were collected using online questionnaires and analyzed using descriptive statistics, Pearson correlation statistics, and stepwise multiple regression. The results showed that most of the samples had a good level of self-protection from COVID-19 infection (93.25%). Knowledge of infection and transmission, perception of severity, perception of risk in infection and transmission, expectation on outcomes of prevention, and expectations regarding self-efficacy in prevention were statistically significantly related to self-protection from COVID-19 infection among the residents (p-value <0.001). Although there were new COVID-19 strains, the main concept of prevention remains unchanged, with a good attitude, perception of severity, perception of risk in infection and transmission, and expectation on outcomes of prevention. These factors were motivations that drive residents to self-protection from COVID-19.